(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
Every economical system is a combination of philosophical norms that, implemented in a precise historical moment, bring about a functional structure that remains in force all along a specific period; its operative manifestation at every moment of time is the result of a specific economical model. If the crash of 1929 meant the end, by exhaustion, of the model that began in 1873, the present day systemic crisis has shown the exhaustion of the model that began after World War II. These are crisis years in which a new model is being created with a view to become adequate for the needs of coming years.